Comparison of Transtibial and Tibial Inlay Techniques for Posterior Cruciate Ligament Reconstruction with an Average of 10 Year- Follow-up. Issue 7 (29th July 2014) - Seon, Jong Keun; Song, Eun Kyoo; Park, Hyoungwon
Objectives: We performd this study to determine the long-term results based on clinical and radiographic outcome comparison following either transtibial or tibial inlay technique, and to find out factors related to osteoarthritis after PCL reconstruction. Methods: Seventy-seven patients (77 knees) treated with the PCL reconstruction for chronic injuries constituted the study cohort. The 77 patients were divided into 2 groups, namely, transtibial (44 patients) and tibial inlay (33 patients). The mean time from injury to reconstruction was 12.2 months (range, 2 to 60 months), and their average follow-up was 142 months (range, 97 to 192 months). Outcomes were measured using Lysholm knee scores, Tegner activity scores, laxity test using Telos device, and development of osteoarthritis. Results: There was significant improvement of Lysholm knee scores, Tegner activity scores, and laxity test using Telos device between the preoperative values and final follow-up values ( P < .05). However, there was no significant difference in the final follow-up outcomes ( P > .05). The final follow-up radiographs according to International Knee Documentation Committee guidelines showed that 7 patients (22.7%) in transtibial group and 4 patients (18.2%) in tibial inlay group were rated as Grade C. We found correlation between meniscectomy and osteoarthritis, but other factors including reconstruction technique, sex, age, and posterior instability did not influence the arthritic changes in both groups (Fig 1). Conclusion: The clinical and radiographic outcomes between the two surgical techniques of PCL reconstruction were comparable. Osteoarthritis was observed in some patients with a significant proportion showing some loss of joint space, and factors except meniscectomy did not show correlation with development of osteoarthritis.